Microstructure Evolution in Al-5.7Si-2Cu-0.3Mg alloy by Reheating in High-Frequency Induction Heating for Thixoforming Process - Samat, Saziana; Omar, Mohd Zaidi; Mohamed, Intan Fadhlina; Arif, Mohd Anif Mohd (International Journal of Engineering and Technology, 2018)
Thixoforming is a forming and shaping process of metal components in their semi-solid state. It can produce a near net shape product with fine globular microstructure and is highly reliable. The process involves preparing the feedstock material with non-dendritic microstructure, heating and consequently forming. The most important step to produce a successful product is reheating of the feedstock material in its semi-solid state and this is mainly achieved by induction heating, which guarantees precise and rapid heating. Thus, this paper discusses the high-frequency induction heating system utilised for this important reheating step. An approximation method of coil geometry is adopted to evaluate the operating condition on the coil current as an input parameter. Microstructural evolution of Al-Si-Cu-Mg at different liquid fraction corresponds to 35% to 50% liquid fraction at 575°C to 600°C was analysed. The result of the image analysis showed a transformation of dendritic, to a spherical morphology. All the microstructures in the semi-solid state range from 35% to 50% liquid fraction contain the primary α Al-globular grain surrounded by the uniformly distributed eutectic silicon. It was found that less entrapped liquid, uniform globule size, higher spherical morphology, shorter heating time and billet stability were obtained at 35% liquid fraction of 575°C with an average shape factor and globule size of 0.73 and 45.8 μm, respectively